G-CSF plasma levels in clozapine-induced neutropenia - Jauß, Jan Marek; Pantel, Johannes; Werle, Egon; Schröder, Johannes (Biological psychiatry, 2000)
Background: Clinical reports emphasize the therapeutic usefulness of granulocyte colony-stimulating factor (G-CSF) in clozapine-induced granulocytopenia. Only sparse information exists, however, on the natural course of endogenous G-CSF plasma levels in this condition. Methods: We monitored G-CSF and white blood cell (WBC) counts in a 73-year-old patient who developed granulocytopenia while being treated with clozapine for schizoaffective disorder. Clozapine treatment was discontinued immediately, and G-CSF serum levels were determined repeatedly during the clinical course. Results: Whereas WBC counts increased again within 6 days after discontinuation of clozapine, G-CSF level decreased significantly within the same period. The rapid decrease of endogenous G-CSF levels paralleled by a normalization of neutrophil count was interpreted as the result of an intact regulatory mechanism of granulocytopoesis. Therefore G-CSF therapy was not initiated. Owing to lack of therapeutic alternatives, it was decided to reintroduce clozapine. G-CSF levels decreased further, accompanied by an increase of WBCs, indicating stable bone marrow functioning. Conclusions: Based on this observation, we assume that the course of G-CSF and WBC counts indicated an abortive form of toxic bone marrow damage with subsequent recovery. We conclude that monitoring of G-CSF levels may serve as a useful tool in the follow-up of patients in whom clozapine-induced bone marrow damage is suspected.